2011
DOI: 10.1007/s00167-011-1510-4
|View full text |Cite
|
Sign up to set email alerts
|

Two continuous femoral nerve block strategies after TKA

Abstract: The study group who received 7-day continuous femoral nerve block after TKA showed superior analgesia and higher patient satisfaction during the hospital stay than those given 3-day continuous femoral nerve block. Despite the additional time, effort and cost to place and manage continuous femoral nerve catheters, the 7-day continuous femoral nerve block can be recommended as an effective and safe regional component of a multimodal analgesia strategy after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The occurrence of infections have been rarely reported in various studies (7, 21) but destructive effects of infection in arthroplasty can make it very difficult to justify even in a single case. In a study (22), femoral catheter was followed by superficial infection in 2 patients. In another study (23), although no infections were reported but bacterial colonization in 57% of patients was noted.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of infections have been rarely reported in various studies (7, 21) but destructive effects of infection in arthroplasty can make it very difficult to justify even in a single case. In a study (22), femoral catheter was followed by superficial infection in 2 patients. In another study (23), although no infections were reported but bacterial colonization in 57% of patients was noted.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, approximately 700,000 total knee arthroplasty (TKA) procedures were performed in 2010, and this number is expected to grow to 3.5 million procedures per year by 2030 . Approximately half (30% to 90%) of all TKA patients experience moderate to severe pain during the first month after TKA surgery, and over half remain on opiates during this time frame . Additionally, up to 35% of patients experience moderate to severe chronic pain of greater than 2 months following surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Adequate and effective pain relief is requested, mainly to improve patient satisfaction, to expedite mobilization and rehabilitation, to decrease the duration of hospital stay, and consequently to lower the risk of deep vein thrombosis or nosocomial infections [24]. Femoral nerve block (FNB) could provide effective analgesia and is a well-accepted method for regional anesthesia following TKA [5, 6]; however, some patients still experienced significant postoperative pain. Compared with FNB, local infiltration anesthesia (LIA) is an alternative and cost-effective anesthetic technique which has been promoted for a few decades and shows excellent outcome for pain relief after TKA [7, 8].…”
Section: Introductionmentioning
confidence: 99%